Influence of Project-Based Learning Model To Increase Cadet Creativity In Politeknik Penerbangan Surabaya: Literatur Review - Jamaludin; I Wayan Susila; Any Sutiadiningsih; Suparji; Lilik Anifah (Publisher Cv. Inara, 2021)
This article is to describe the Project-Based Learning Model that is applied to enhance the cadet creativity in Politeknik Penerbangan Surabaya. Project-based Learning (PjBL) is effective Learning applied because it emphasizes contextual Learning through complex activities. The focus of Learning lies in the concepts that involve cadets in problem-solving investigations and task activities to develop creativity, provide opportunities for cadets to work autonomously to construct their own knowledge, and reach their peak, which is to produce tangible products. The purpose of this study was to find out how the role of the PBL learning model was in increasing the creativity of the cadets in Politeknik Penerbangan Surabaya. This research is a descriptive study by collecting data through literature studies. Usage of the application of a good PjBL learning model will increase the creativity of cadets in working on projects that have been planned. The results of literature studies from various relevant journals obtained data that the PjBL learning model is effective in enhancing creativity.